Evaluation of Academic, Referring to the Determination of the Implementation of Evaluation, Control, and Improvement at the School of Economics Balikpapan. - Surman, Surman; Hidayat, Dasrun (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
The implementation of higher education evaluation in Indonesia is closely related to the implementation of the Internal Quality Assurance System (SPMI). Several previous studies that highlighted the implementation of SPMI in higher education often encountered problems, including the lack of relevance of the education process to stakeholder needs or the lack of availability of human resources, especially auditors to support SPMI, but these studies were less specific in highlighting academic SOPs as part of the managerial strategy for developing SOPs in higher education. Therefore, this study aims to evaluate and see the strategy for developing academic SOPs at STIE Balikpapan by referring to the Determination of the Implementation of Evaluation and Improvement Control (PPEPP). The form of research conducted was qualitative with a descriptive approach through a case study design. Based on the results of the research conducted, it was found that the implementation of academic SOPs at STIE Balikpapan has generally been implemented, and has been socialized using internal media, monitoring of academic SOPs has been running but needs to be carried out in a planned, structured and specific manner, evaluation of academic SOPs is carried out by the internal quality assurance unit in the form of audits per semester, but has not been carried out comprehensively in all fields or work units in the academic scope. The academic SOP development strategy model implemented at STIE Balikpapan has been running, but has not fully referred to the existing PPEPP standards, the development strategy still focuses on certain SOPs, namely the curriculum, and is still flexible, namely adjusting to needs that are considered urgent.